Linux und Freie Software: Eine Entmystifizierung - Winzerling, Werner (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
Since the great success of the operating system Linux, the development of Free and Open Source Software is broad discussed. This is also seen as the beginning of a new economic development. This paper examines, what makes Linux actually so significant for the computer industry. First Linux is critical evaluated and placed opposite the Microsoft operating systems. Than some substantial new influences on the development and production in the computer industry are worked out. On the one hand this are modifications in the production chain of computers and on the other hand network effects (externalization), which proceed from these products. On the basis of this new economic situation the Linux phenomenon is explained and it is shown from which the great importance of Microsoft in the computer industry results at present.